Persepsi Masyarakat Muslim Paleteang Pinrang terhadap Eksistensi Bank Syariah - sri wahyuni ibrahim (Institut Agama Islam Negeri Parepare, 2021)
Perception is a process that involves the entry of messages or information in the human brain continuously in contact with the environment through the senses. One of the reasons why perception is so important when it comes to interpreting our surroundings is that each of us perceives but perceives differently. For this reason, this study aims to find out how the public's perception of the existence of Islamic banks in Pacongang Village, Paleteang District, Pinrang Regency and the factors that influence perceptions in determining the choice of Islamic banks. The results of this study indicate that the public's knowledge of Islamic banks, most of the people only know about Islamic banks without understanding it. There are still many people who do not understand the concept of Islamic banking. While there are 2 factors, namely internal and external factors that affect perception. Where internal factors include the value offered by Islamic banks, while those included in external factors are the lack of information reaching the public and the difficulty of finding Islamic banks. Keywords: Kafalah, Guarantee, Sharia Banking